2021
DOI: 10.1093/jas/skab216
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic parameters for Aleutian disease tests and their correlations with pelt quality, reproductive performance, packed-cell volume, and harvest length in mink

Abstract: Aleutian disease (AD), caused by the Aleutian mink disease virus (AMDV), is a major health concern that results in global economic losses to the mink industry. The unsatisfactory outcome of the culling strategy, immunoprophylaxis, and medical treatment in controlling AD have urged mink farmers to select AD resilient mink based on several detection tests, including enzyme-linked immunosorbent assay (ELISA), counterimmunoelectrophoresis (CIEP), and iodine agglutination test (IAT). However, the genetic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Interestingly, the variation in feed intake was important for the CIEP classification, which might be because of the inconsistency in the diet of infected mink. Sex and color type were less important for the CIEP classification, which was also supported by our previous study that these effects were not significantly affecting the CIEP [ 33 ].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, the variation in feed intake was important for the CIEP classification, which might be because of the inconsistency in the diet of infected mink. Sex and color type were less important for the CIEP classification, which was also supported by our previous study that these effects were not significantly affecting the CIEP [ 33 ].…”
Section: Resultssupporting
confidence: 80%
“…The importance of the ELISA is expected as the ELISA systems are also alternative methods for the diagnosis of AD [ 46 ]. Previously, we also reported that the ELISA tests had significant phenotypic and genetic correlations with CIEP [ 33 ]. The age at sampling might be an important feature for CIEP since, if animals stayed on the farm for a longer period of time, they might have a higher chance of being infected by the AMDV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected mink that remained healthy (non-progressive infection) have long been known to have low antibody titers [ 15 , 16 , 17 ]. Antibody titer is also negatively associated with reproductive performance [ 18 , 19 ], thus, implying that selection for low antibody titers is a logical approach for establishing tolerant herds. Development of enzyme-linked immunosorbent assay (ELISA) systems [ 20 , 21 , 22 ] has facilitated antibody titer measurement for the identification of tolerant mink, and a combination of weak ELISA positive and normal litter size was effective in reducing the incidence of clinical forms of the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, genetic selection for pelt quality traits requires estimating the heritabilities as well as the phenotypic and genetic correlations among these traits. Several studies have estimated the genetic parameters and heritabilities for live grading traits in American mink populations [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, heritabilities for dried pelt quality traits and their genetic correlations with live grading traits and body weight and length traits have rarely been reported [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%